MANAGEMENT APPROACHES AND APPLICATION AREAS OF INFORMATION SECURITY IN ORGANIZATIONS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In organizations, two types of communication can be distinguished, predetermining approaches to Information Security (IS): communication based on equality - "Network communication" (Networks from/in organizations) and "Hierarchical organizational communication". A primary task of IS in an organization is to protect sensitive data in both types of communication. The IS approach must be tailored and cover all options – a holistic approach. Existing IS management approaches can be divided into two large groups: Information security approaches in Network Communications and data security approaches in Hierarchical Organizational Communication. Approaches to managing IS in network communications include Firewalls, Intrusion Detection Systems (IDS), Intrusion Prevention Systems (IPS), Anti-Virus, Anti Malware, Endpoint Protection, Perimeter Security and Cyber-threat intelligence systems. IS management approaches in Hierarchical Communication include Data Classification and Data Leakage Prevention (DLP) systems. In the article are examined the areas of application of the different approaches to information security in an organization - External network, Network Perimeter, Internal network, Computer equipment, Applications and Data.